The Effect of Project-Based Learning on Children's Mathematical Ability and Social Skills in Kindergarten - Yesi Susanti; Nurhafizah; Setiyo Utoyo; Serli Marlina (Postgraduate, University of Mataram, 2026)
This study aims to analyze the effect of Project-Based Learning (PjBL) on improving early childhood mathematical abilities and social skills among children aged 5–6 years. The research employed a quantitative approach using a quasi-experimental design with a non-equivalent control group pretest–posttest design. The sample consisted of 74 kindergarten students divided into experimental and control groups. Data were collected through performance tests to assess mathematical abilities and observation sheets to measure social skills. Data analysis was conducted using the non-parametric Wilcoxon test. The results indicate a significant improvement in the experimental group compared to the control group. The average mathematical ability score increased from 12.54 (pretest) to 27.35 (posttest), with the highest N-Gain (0.87) observed in the counting indicator. Similarly, social skills improved from an average score of 1.24 to 2.79, with the highest N-Gain (0.92) in communication aspects. Statistical analysis revealed a significance value of p < 0.001, indicating that the implementation of PjBL had a statistically significant effect. These findings suggest that PjBL facilitates meaningful and contextual learning experiences, enabling children to construct mathematical understanding through concrete activities while simultaneously enhancing social interaction through collaborative tasks. In conclusion, Project-Based Learning is an effective and developmentally appropriate approach for improving both mathematical abilities and social skills in early childhood education settings.